Rizal and "The Philippines, A Century Hence" a retrospective construction of Rizal's notions of liberty and progress in the context of colonialism and resistance - Diel, Soeren D. . (1997.)
The first glance, Rizal's the Philippines, a century hence appears to be nothing more than a polemical essay directed against the Philippine colonial status quo under Spain. a legitimate act of resistence through propaganda, against the excesses of colonial power. However, further analysis of Rizal's text reveals underlying doscourses that determine its very existence, the mode by whjich it operates and the means by which it legitimizes itself. These discourses sorround notions of liberty and progress first put forward by the philiosphies of the 18th century European Enlightenment. These notions furniched Rizal with an idiom of resistance against colonial power, precisely because they apparently stood in stark contrast to the frustrating conditions of the colony. For Rizal, the colonial government practiced a policy that was everything but libertian and progressive. Rizal?s clach with the colonial authorities was an instance of conflict between the progressive and the reactionary. This thesis asserts that power and resistance are not to be viewed as oppositional forces; rather they combine to both subvert and support each other. Through his writings, including The Philippines, a century hence, Rizal was a contender in the completion of discourses; liberty and progress versus colonial power and policy. This discursive tension was by no means limited to colonial Philippines. There were larger discursive upheavals (including revolutions) in Europe during and since the Enlightenment era. My contention is that Rizal and his contemporaries first had to acquire the specifically Western discursive articulation of liberty and progress before he could launch a campaign against the rep[ressive and obscurantist colonial government. Rizal indeed had to become ?fgporeign? before he could imaghine the ?Filipino nation?. These views further lead to the conclusion that Rizal should not be viewed as an in dependent and sovereign agent of resistance against colonialism; rather he was a player embedded within the larger discursive framework of European politics. The rereading of Rizal put indiscriminate anti-colonialism in a critical position, sunce by genealogy such ?counterdiscourses? are shown to be rooted in the very thing they set out to reject.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 1997.
Keywords: Rizal, Jose -- Colonialism and resistance